The inside story - Buckley, Michael, 1969- (Buckley, Michael, 1969- Sisters Grimm, 2010)
Sabrina, Daphne, and Puck, stuck in the Book of Everafter, chase the Master through a series of stories, where they're willing to change what they need in order to save their baby brother. Soon, however, they are confronted by the Editor--the book's guardian--who, along with an army of tiny monsters known as Revisers, threatens the children with dire consequences if they don't stick to the stories. Faced with a challenge like this, will they be able to find their brother in time?